К вопросу о влиянии взаиморасположения резцов на энергоемкость разрушения горной породы - Майстренко, А.Л.; Заболотный, С.Д.; Виноградова, Е.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Results of studies of dependence between arguments of interposition of chisels on a cutting
head of a heading machine and specific energy of breaking down of rock of type of Terebovljansky
sandstone are resulted. Optimum arguments of rock breaking proceeding from the minimum energy
output are determined at the max output of its breaking down by chisels of type RP-221.